Impact of bio-stimulants on organically cultivated strawberries(Fragaria × ananassa Duch.) - Bhowmick, N; Bhujel, S; Rai, S; Layek, S; Mostafa, Md (Journal of Horticultural Sciences, 2025)
The present study evaluated the effect of different foliar-applied biostimulants on growth, yield and fruit quality of organically cultivated strawberry cv. Festival under protected conditions in the Darjeeling Himalayan region during a single growing season (2021-22). Four biostimulants seaweed extract, humic acid, fulvic acid and amino acid were applied either once (30 days after transplanting, DAP) or twice (30 and 60 DAP), along with a water sprayed control in randomized block design with three replications. Foliar application of humic acid at 4 gL-¹ twice (30 and 60 DAP) significantly enhanced vegetative growth, flowering duration, fruit set, yield and biochemical quality. The highest fruit yield (650.10 g plant-¹), total soluble solids (9.73 °Brix) and ascorbic acid content (50.48 mg 100 g-¹) were recorded under this treatment, along with reduced titratable acidity. The findings indicate that humic acid applied twice during early growth stages can be effectively integrated into organic strawberry production systems in the Darjeeling Himalayan region for improving productivity and fruit quality.